Geographic Legacy: Remembrance of the Pioneers of the School of Geographic Sciences at the National University, Costa Rica - Orias Arguedas, Lidia (2024)
This article examines the memory and legacy of the pioneers of the School of Geographic Sciences. By employing the term “Geographic Legacy,” it underscores the heritage and enduring influence these individuals have imparted to the field of geography. The inclusion of “Remembrance of the Pioneers” honors the visionary role of those who initially paved the way, establishing the foundations of knowledge within this educational institution.